Biosurfactant production by yeasts from different types of soil of the South Shetland Islands (Maritime Antarctica) - Bueno, J. L.; Santos, P. A.D.; da Silva, R. R.; Moguel, I. S.; Pessoa, A.; Vianna, M. V. [UNESP]; Pagnocca, F. C. [UNESP]; Sette, L. D. [UNESP]; Gurpilhares, D. B. (Oxford University Press (OUP), 2019)
Aim: To screen and identify a potential biosurfactant-producing yeast strain isolated from Antarctic soil and to evaluate the fermentation process kinetics of the most promising strain on biosurfactant production using glycerol as carbon source. Methods and Results: From the 68 isolated yeast strains, 11 strains were able to produce biosurfactants after Emulsification Index (E.I.) and Drop Collapse tests, reaching an E.I. higher than 10%. Strain 1_4.0 was the best producer, identified as Candida glaebosa based on molecular analysis. Yeast was cultivated in a medium composed of glycerol supplemented with yeast extract for 120 h to determine the process kinetics. The increased C/N ratio affected yeast growth and biosurfactant production. Biosurfactant release was associated with the end of exponential and beginning of the stationary growth phases. Results indicated an E.I. of 30% at the end of the fermentation. Conclusions: The feasiability of C. glaebosa to produce biosurfactant from a low-cost medium cultivation shows a great impact on the development of bioresource in the Antarctica terrestrial environment. Significance and Impact of the Study: Although the diversity of psychrophilic/psychrotolerant micro-organisms from Antarctica has been the preferred subject of study by microbiologists, terrestrial microfungal communities are scarcely investigated and literature about the biotechnological potential of such micro-organisms should cover important biomolecules in addition to cold-adapted enzymes. In the present study, for the first time, the Maritime Antarctica environment was screened as a novel source of biosurfactants produced by micro-organisms.
Keywords: Antarctica; biosurfactant; emulsification index; micro-organisms; yeast